Analisis Pengaruh Indikator Keuangan dan Makro Ekonomi terhadap Profitabilitas Bank Pembangunan Daerah di Masa Sebelum dan Selama Pandemi Covid-19 - Praja, Eka Satria; Adrianto, Fajri; Hamidi, Masyuri (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to see the effect of NPL, LDR, CASA, GRDP and inflation on the profitability of 26 (twenty six) Regional Development Banks (BPD) throughout Indonesia which were presented in the form of ROA ratios for the period before the Covid pandemic in 2016 to 2019 and during the Covid pandemic from 2020 to 2021. The descriptive research method uses a quantitative approach with the data analysis method used i is panel data regression analysis. The type of data used is secondary data sourced from published financial reports of BPDs throughout Indonesia on the websites of each BPD, the Central Bureau of Statistics and Bank Indonesia. This research got partial results before the Covid pandemic; NPL has a significant negative effect on ROA, LDR has no significant positive effect on. CASA has no significant positive effect on ROA. GRDP has no significant positive effect on ROA. Inflation has no significant negative effect on ROA. Simultaneously NPL, LDR, CASA, GRDP and inflation have a significant effect on ROA. Partial research results during the Covid pandemic; NPL has no significant negative effect on ROA. LDR has no significant positive effect on ROA. CASA has no significant positive effect on ROA. GRDP has no significant positive effect on ROA. Inflation has no significant negative effect on ROA. Simultaneously NPL, LDR, CASA, GRDP and inflation have no significant effect on ROA.